2015
DOI: 10.1111/oik.02000
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐temporal factors influence predation for polar bears in a changing climate

Abstract: Predation is an ecological interaction infl uenced by abiotic and biotic factors acting on multiple temporal scales, yet multi-temporal comparisons are rare in empirical studies. For polar bears Ursus maritimus , the physical confi guration of the habitat and conditions in which seals are hunted may change on intra-and inter-seasonal scales. Additionally, while the eff ects of climate change on polar bears have focused on linking reductions in sea ice to body condition and survival, the potential changes to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 63 publications
2
31
1
Order By: Relevance
“…Pilfold et al (2015) similarly documented impacts of wind speed on polar bear predation success and wind has been documented as an important factor for successful predation in other species (Funston, Mills, & Biggs, 2001;Nevitt, Losekoot, & Weimerskirch, 2008). The probability of a predation event for polar bears and ringed seal body condition from the eastern Beaufort Sea have both been shown to have significant relationships with the AO and AOO (Pilfold et al, 2015;Nyugen et al, 2017). These results are consistent with our finding that the winter AO in the Beaufort Sea was correlated with fasting probability.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Pilfold et al (2015) similarly documented impacts of wind speed on polar bear predation success and wind has been documented as an important factor for successful predation in other species (Funston, Mills, & Biggs, 2001;Nevitt, Losekoot, & Weimerskirch, 2008). The probability of a predation event for polar bears and ringed seal body condition from the eastern Beaufort Sea have both been shown to have significant relationships with the AO and AOO (Pilfold et al, 2015;Nyugen et al, 2017). These results are consistent with our finding that the winter AO in the Beaufort Sea was correlated with fasting probability.…”
Section: Discussionmentioning
confidence: 93%
“…Although wind speed did not vary across subpopulations, speed increased between periods and could affect polar bear fasting behavior via declines in haul-out duration of seals (Carlens, Lydersen, Kraffft, & Kovacs, 2006) or disruption of polar bears' olfactory cues (Togunov, Derocher, & Lunn, 2017). Pilfold et al (2015) similarly documented impacts of wind speed on polar bear predation success and wind has been documented as an important factor for successful predation in other species (Funston, Mills, & Biggs, 2001;Nevitt, Losekoot, & Weimerskirch, 2008). The probability of a predation event for polar bears and ringed seal body condition from the eastern Beaufort Sea have both been shown to have significant relationships with the AO and AOO (Pilfold et al, 2015;Nyugen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, Mauritzen et al [12] found that the probability of using high sea ice concentrations decreased when bears were located in areas with high sea ice concentrations, but exhibited the opposite pattern when bears were in areas with low concentrations of sea ice. Polar bears live in a highly dynamic environment, requiring them to respond by constantly moving to areas with conditions suitable for finding and capturing prey [16,36]. The lack of change in functional responses between periods implies that polar bears are making similar decisions in response to their local conditions as they did before sea ice changes.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial overlap between polar bears and whelping ringed seals likely influences a change in the age-class proportions of kills, as polar bears respond to the availability of vulnerable pups. Exploring the assumptions of common analytical modelling approaches in ecology, Pilfold et al (2015) showed that including biologically relevant measures, such as the size of kills, provided significant improvement to the models in both fit and interpretation. Measuring only the occurrence of an ecological event, whether temporally or spatially was insufficient when validated against independent data.…”
Section: Polar Bear Foraging Ecology In the Beaufort Seamentioning
confidence: 99%